Pediatric ARDS biomarkers: missing the random forest for the trees - Yehya, Nadir (Critical care (London, England), 2019)
[...]mortality is much lower in pediatric ARDS, which is why it is rarely chosen as the primary outcome in trials. [...]this logical proposal confronts the reality that bronchoalveolar lavage sampling of ARDS in children is far rarer than in adults and would require extensive resources and practice change. [...]a biomarker specific for pediatric ARDS remains elusive, and we continue to rely on clinical criteria for diagnosis and prognostication [12]. In the near future, pediatric critical care may not be caring for children with sepsis, ARDS, traumatic brain injury, or post-cardiac arrest syndrome; rather, we may be discussing angiopoietin-dysregulated endotheliopathy, sRAGE-positive organ failures, and human-leukocyte antigen DR-deficient immunosuppression. [...]the argument regarding how to advance the promise of precision medicine is not whether we should be better lumpers or splitters, but whether we should radically change how we view our patients. Am J Physiol Lung Cell Mol Physiol. 2016;310(3):L224–31.View ArticleGoogle Scholar Orwoll BE, Spicer AC, Zinter MS, Alkhouli MF, Khemani RG, Flori HR, Neuhaus JM, Calfee CS, Matthay MA, Sapru A. Elevated soluble thrombomodulin is associated with organ failure and mortality in children with acute respiratory distress syndrome (ARDS): a prospective observational cohort study.